Bridging the Gap Between Continuous Sedation Until Death and Physician-Assisted Death: A Focus Group Study in Nursing Homes in Flanders, Belgium. (June 2015) - Rys, Sam; Deschepper, Reginald; Mortier, Freddy; Deliens, Luc; Bilsen, Johan
The distinction between continuous sedation until death (CSD) and physician-assisted death (PAD) has become a topic of medical ethical debate. We conducted 6 focus groups to examine how nursing home clinicians perceive this distinction. For some, the difference is clear whereas others consider CSD a form of euthanasia. Another group situates CSD between pain relief and ending life. Arguments for these perspectives refer to the following themes: intention, dosage of sedative drugs, unconsciousness, and the pace of the dying process. Generally, CSD is considered emotionally easier to deal with since it entails a gradual dying process. Nursing home clinicians have diverging perceptions of the relation between CSD and PAD; some consider CSD to be more than a purely palliative measure, that is, also as a means to hasten death.